Medium optimization for polyhydroxyalkanoate production by Pseudomonas pseudoalcaligenes strain Te using D-optimal design. (March 2019) - Zihayat, Bahare; Shakibaie, Mojtaba; Sabouri-Shahrbabak, Saleheh; Doostmohammadi, Mohsen; Ameri, Atefeh; Adeli-Sardou, Mahboubeh; Forootanfar, Hamid
Abstract: The hazardous effects of synthetic polymers encouraged investigators to find about biodegradable polymers among which microbial derived polyhydroxyalkanoate (PHA) have got attention during the two last decades. In the present study, isolation and identification of a PHA producing bacterial strain and optimization of cultural conditions for PHA biosynthesis were aimed. Several soil and spring samples were collected and screened for PHA producing bacterial strain according to the reported protocols. The most efficient isolate was identified using biochemical, morphological, and 16S rDNA gene sequencing methods. The related PHA production was then optimized using D-optimal statistical design. The obtained results of screening step using Nile blue containing culture plate together with biochemical and morphological studies as well as 16S rDNA gene analysis introduced Pseudomonas pseudoalcaligenes strain Te as the most efficient PHA producer. Evaluation of PHA productivity profile of P. pseudoalcaligenes strain Te revealed that maximum PHA biosynthesis was achieved at the stationary phase of growth. Assessment the influence of five parameters on PHA productivity of the selected strain revealed the significant effect of three factors including pH, K2 HPO4, and temperature. The optimum level of these three factors (pH 8.6; K2 HPO4, 4.7 g/L; and temperature of 25 °C) enhanced the PHA production to 5412.9 mM. Although, the capability of P. pseudoalcaligenes for PHA production was confirmed in the present study, it merits further investigations to find about the related pathways involved in PHA biosynthesis by this strain. Highlights: A potent polyhydroxyalkanoate producer bacterium was screened from local springs. The isolated strain was identified as Pseudomonas pseudoalcaligenes strain Te by 16S rDNA gene analyses. The selected model by D-optimal method can predict the best condition for higher biosynthesis of polyhydroxyalkanoate.